If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying -3 + -1y = -15 Solving -3 + -1y = -15 Solving for variable 'y'. Move all terms containing y to the left, all other terms to the right. Add '3' to each side of the equation. -3 + 3 + -1y = -15 + 3 Combine like terms: -3 + 3 = 0 0 + -1y = -15 + 3 -1y = -15 + 3 Combine like terms: -15 + 3 = -12 -1y = -12 Divide each side by '-1'. y = 12 Simplifying y = 12
| 7n^2+37n+20=4n | | 4X(w+3)=w-15 | | y=10x+140 | | -4(3x-1)-2x+5=121 | | 200.96=3.14*D | | 2a+5b=7 | | 7u/5=42 | | X=1.571428571 | | 400x+200=350x+850 | | 9e^11x=11 | | -3x+-5=2x | | 270.04=3.14*D | | 9(x-9)=-18 | | 2x+76=90 | | 10.50=1.50+2n | | 5(2y-4)=-10 | | 2.6=x/(2-2x) | | 5x+24=3 | | -(-7x-5)+8x-10= | | 2x+5(5x-14)=97 | | 14*20-6(20+3)=20+9 | | 2/3=10/e | | 5x-4x=-6x+4 | | 3(7x+2)(x-1)=0 | | =56x^7+21x^4+63x^3 | | 4(x-1)-3x=-2x-4+3 | | 2(r/3-7)=30 | | 3x^3-8x^2-20x+16=0 | | 7y+26=180 | | 6x+14+90+94=180 | | 10m-13m+5+11m=21 | | 20x=40+10x |